Iron, zinc, copper and magnesium nutritional status in Mexican children aged 1 to 11 years Estado nutricio de hierro, zinc, cobre y magnesio en niños mexicanos de 1 a 11 años de edad - Ma. del Carmen Morales-Ruán; Salvador Villalpando; Armando García-Guerra; Teresa Shamah-Levy; Ricardo Robledo-Pérez; Marco Antonio Ávila-Arcos; Juan A. Rivera (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To describe the micronutrient nutritional status of a national sample of 1-11 year old Mexican children surveyed in 2006 in National Health and Nutrition Survey (ENSANUT 2006) and their association with dietary and sociodemographic factors. MATERIALS AND METHODS: Serum samples were used (n=5 060) to measure the concentrations of ferritin, transferrin receptor, zinc, copper and magnesium. RESULTS: Prevalence of deficiencies in 1-4 and 5-11y old children were for iron (using low ferritin) 26.0 and 13.0%; zinc, 28.1 and 25.8%, respectively; and copper, ≈30% in both age groups. Magnesium low serum concentrations (MLSC), were found in 12.0% and 28.4% of the children, respectively. Being beneficiary of Liconsa (OR=0.32; C.I.95%, 0.17-0.61) or belonging to higher socioeconomic status (OR=0.63; C.I.95%, 0.41-0.97) were protective against iron deficiency. Increasing age (OR=0.59; C.I.95%, 1.19-1.32) and living in the Central Region (OR=0.59; C.I.95%, 0.36-0.97) were protective against MLSC. CONCLUSIONS: Deficiencies of iron and zinc are serious public health problems in Mexican children. OBJETIVO: Describir el estado nutricio de micronutrimentos en niños de 1-11 años de edad de la Encuesta Nacional de Salud y Nutrición 2006 y su asociación con factores dietéticos y sociodemográficos. MATERIAL Y MÉTODOS: Se usaron muestras séricas (n=5060) para medir las concentraciones de ferritina, receptor de transferrina, zinc, cobre y magnesio. RESULTADOS: La prevalencias de deficiencias en niños de 1-4 y de 5 a 11 años fueron para ferritina, 26.0 y 13%; zinc, 28.1 y 25.8% respectivamente y cobre ≈30% en ambos grupos. Las concentraciones bajas de magnesio (CBM) fueron 12.0 y 28.4%, respectivamente. Ser beneficiario de Liconsa (RM=0.32; IC 95%: 0.17-0.61) y pertenecer al nivel socioeconómico alto (RM=0.63; IC, 95%: 0.41-0.97) fueron protectores para deficiencia de hierro. La edad (RM=1.26; IC, 95%: 1.19-1.32) y vivir en la región Centro (RM=0.59; IC, 95%: 0.36-0.97) fueron protectores para CBM. CONCLUSIONES: Las deficiencias de hierro y zinc son serios problemas de salud pública en niños mexicanos.